Professionalizing Leadership Debating Education, Certification and Practice (Springer International Publishing, 2018)
This engaging book presents a lively debate surrounding the professionalization of leadership. With contributions from both sides of the argument, the book considers the historical overview of leadership and management as a profession, questions what constitutes a profession, and critically addresses the practicality of professionalizing leadership. With a vast range of perspectives including political philosophy, behavioural professionalism, limits to the professionalization of management and its historical contexts, the book intends to facilitate further discussion on the issues at stake and allow the reader to situate their point of view within the wider debate. With a number of education programs beginning to focus on the art and practice of leading people this debate is very timely, considering the suitability of this approach within management education.